Parents, preschoolers, and napping: the development and psychometric properties of two Nap Belief Scales in two independent samples - Newton, Adam T.; Reid, Graham J. (Frontiers in Sleep, 2024)
Most children cease napping between 2-5-years-old. Little is known about the predictors of this cessation. Parents' sleep-related beliefs aid in understanding children's night-time sleep behaviors, but few index daytime sleep beliefs. Two measures of parents' napping beliefs were developed and evaluatedthe Parents' Nap Beliefs Scale (14-items); the Reasons Children Nap Scale (19-items). Canadian parents of 1-5-year-old children completed these questionnaires and other sleep-related measures in independent pilot (n = 201) and replication (n = 702) samples. In the replication sample, a subsample of parents also completed 1-3 weeks of daily sleep diaries. The samples were representative of the Canadian population by ethnicity and region. In both samples, both measures demonstrated strong construct validity, convergent and divergent validity, and internal consistency. The Parents' Nap Beliefs Scale was comprised of two factors: (a) Positive Beliefs and (b) Negative Beliefs about napping. The Reasons Children Nap Scale was comprised of two higher order factors and five lower order factors: (a) Encouragement Reasons (Child-related; Parent-related) and (b) Discouragement Reasons (Child prefers not to nap; Child functions well without a nap; Scheduling). Future research should: (a) test these scales as longitudinal determinants of children's nap behavior and cessation; (b) evaluate parental nap beliefs in non-Western cultures; and (c) adapt these scales for use with childcare providers.